Teachers' Efforts to Develop the Language of 5-6 Year Old Children Through Picture Books - Lestari, Puji; Muhammad Yusuf; Ferdian Utama; Hanafiah, Nur Arifah (Bulletin of Early Childhood, 2025)
This study aims to determine the effectiveness of storytelling methods using picture story books in developing the language skills of children aged 5-6 years at the Qur'an Ma'arif Kindergarten Sumber Rezeki Mataram. The study was conducted in the form of Classroom Action Research (CAR) for two cycles, each consisting of three meetings. Data collection techniques included observation, interviews, and documentation, with a focus on five indicators of language skills: speaking with good language, writing names, communicating with teachers and friends, asking and answering questions. The results showed a significant increase in language skills. The average score of children increased from 7.6 (Not Developing) in the pre-cycle, to 16.0 (Developing as Expected) in the first cycle, and reached 23.5 (Developing Very Well) in the second cycle. Learning with picture books has been proven to be able to create a pleasant learning atmosphere, stimulate children's verbal expression, and facilitate the understanding of vocabulary and sentence structure. This study recommends the use of picture story methods as an effective strategy for early childhood education teachers in improving children's language development as a whole.